A method for preparing a novel solid-state battery containing magnesium

By improving the Hummers method, graphene is prepared and combined with magnesium source and polymer solid electrolyte, the problems of poor material structural stability and interface contact in lithium-ion batteries are solved, and the high rate performance and long cycle life of solid-state batteries are achieved.

CN115207447BActive Publication Date: 2025-03-18ZHONGKE HONGTAI (ANHUI) NEW ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210651362.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-09
Publication Date
2025-03-18
Estimated Expiration
2042-06-09

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems with lithium dendrite, volume expansion of silicon-based materials during charging and discharging, and poor interface contact between electrolyte and electrode.

Method used

The expanded graphite was converted into graphene by the improved Hummers method, and the magnesium source, graphene and polymer solid electrolyte were combined by ultrasonic stirring to prepare a new solid-state battery containing magnesium.

Benefits of technology

It significantly improves the rate performance and cycle life of solid-state batteries, reduces the internal diffusion resistance of electrons and ions, and has a simple process and low cost, which is suitable for industrial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115207447B_ABST
    Figure CN115207447B_ABST
Patent Text Reader

Abstract

The present invention discloses a novel solid-state battery containing magnesium, the solid-state battery comprising a positive electrode, a solid electrolyte and a negative electrode; the positive electrode active material in the positive electrode is LiFePO4; the negative electrode and the solid electrolyte are a composite of a magnesium-containing negative electrode active material and a polymer solid electrolyte. The positive electrode active material LiFePO4 in the solid-state battery of the present invention has good cycle stability and can effectively improve the safety of the solid-state battery; the magnesium-containing graphene negative electrode material contains a uniformly dispersed polymer solid electrolyte, which can effectively increase the interface contact area between the negative electrode material and the solid electrolyte and improve the diffusion capacity of lithium ions at the electrode-electrolyte interface. At the same time, the introduction of magnesium ions in the negative electrode material can stabilize the material structure, significantly alleviate the stress generated by the expansion of the material during the charge and discharge process of the solid-state battery, and thus improve the comprehensive performance of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a novel magnesium-containing solid-state battery. Background Art

[0002] Lithium-ion batteries are widely used in various fields such as portable electronic products, electric vehicles and national defense equipment due to their advantages such as high energy density, long cycle life and good rate performance. As an important component of lithium-ion batteries, organic electrolytes have serious safety hazards due to their leakage, poor chemical stability, narrow operating temperature range, flammability and explosion. In addition, the limited voltage window of organic electrolytes also limits their further application in high-voltage battery systems. Looking at the overall development trend of lithium batteries, research on high-performance solid-state lithium-ion batteries is an important development direction for lithium-ion batteries in the next step.

[0003] Solid-state batteries use non-volatile, non-flammable solid electrolytes instead of organic electrolytes, which not only allows them to work in a wide temperature range, but also can solve the safety risks of lithium batteries. At the same time, this type of battery still has the advantages of high energy density, high power density, and long service life. Currently, in the developed solid-state battery systems, commonly used negative electrode active materials include lithium metal and metal compounds, silicon-based materials, and carbon materials. Among them, lithium metal and metal compounds and silicon-based materials are widely used due to their high theoretical specific capacity.

[0004] However, when lithium metal is used as the negative electrode, serious lithium dendrite problems will occur during the charge and discharge process at high rates, causing battery capacity decay and thermal runaway problems; while silicon-based materials produce a large volume expansion (about 400%) during the ion insertion and extraction process, resulting in an increase in the internal resistance of ion migration, which reduces the battery rate and cycle performance. In addition, the poor interface contact between the electrolyte and the electrode will also cause a reduction in the battery rate performance and cycle performance.

[0005] As a kind of carbon material, the application of graphene not only avoids the problem of battery capacity attenuation caused by the generation of lithium dendrites on the material surface, but also alleviates the problem of low electrical conductivity of solid electrolytes. More importantly, it itself belongs to a highly interconnected network structure and has the characteristics of high conductivity, high mechanical strength, good flexibility and excellent chemical stability, which makes the battery have excellent rate performance and cycle life.

[0006] However, it is worth noting that graphene is very easy to stack or even agglomerate during the charging and discharging process, which causes the battery's lithium insertion capacity to decrease, so it cannot be used directly as an electrode.

[0007] CN202111255889.4, CN 202010671088.5 and CN 201911312442.9 have disclosed that the introduction of magnesium ions into electrode materials can not only change the electrical conductivity of the raw materials and the migration rate of lithium ions, but also to some extent solve the structural stability and expansion problems of certain materials during high-rate charging and discharging, thereby significantly improving the overall performance of the battery.

[0008] However, no one has explored the comprehensive performance of the combination of polymer electrolyte, magnesium salt and graphene. At the same time, the above synthesis process is relatively complicated and the uniformity of particle size is difficult to control. Therefore, it is a key task to seek a new type of magnesium-containing solid-state battery with simple process, easy-to-control conditions, low cost and excellent performance. Summary of the invention

[0009] The purpose of the present invention is to solve the problems existing in the above research. Therefore, the present invention provides a method for preparing a novel solid-state battery containing magnesium, which is used to solve the problems of easy aggregation of graphene, low ionic conductivity of polymer solid electrolyte and poor interface contact between electrolyte and electrode.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] One of the purposes of the present invention is to provide a new type of magnesium-containing solid-state battery, which comprises a positive electrode, a solid electrolyte and a negative electrode, wherein the positive electrode active material in the positive electrode comprises LiFePO4, and the negative electrode and the solid electrolyte are a composite of a negative electrode active material containing a magnesium ion source and a polymer solid electrolyte.

[0012] The present invention provides a novel magnesium-containing solid-state battery, which also has the following technical features:

[0013] Furthermore, the magnesium ion source is a soluble magnesium salt, specifically any one of magnesium acetate, magnesium sulfate and magnesium nitrate.

[0014] Furthermore, the precursor raw material of the negative electrode active material is expanded graphite.

[0015] Furthermore, the polymer solid electrolyte includes any one of polyethylene oxide PEO, polyacrylonitrile PAN, polymethyl methacrylate PMMA, polyvinylidene fluoride PVDF, polyvinyl alcohol PVA, polyacrylic acid PAA, polyethylene glycol PEG and polydimethylsiloxane PDMS.

[0016] Furthermore, the novel magnesium-containing solid-state battery is any one of a solid-state lithium-ion battery, a solid-state sodium-ion battery and a solid-state potassium-ion battery.

[0017] Furthermore, the preparation method of the novel solid-state battery containing magnesium comprises the following steps:

[0018] Step 1: LiFePO4, a conductive agent and a binder are mixed to obtain a positive electrode slurry, which is then coated on a positive electrode current collector, and dried and rolled to obtain a positive electrode layer;

[0019] Step 2: Mix the negative electrode active material, the conductive agent and the binder to obtain a negative electrode slurry, and apply the negative electrode slurry on the negative electrode current collector, and obtain a negative electrode layer after drying and rolling;

[0020] Step 3: Assemble the positive electrode layer, negative electrode layer and polymer solid electrolyte obtained in steps 1 and 2 into a new solid-state battery containing magnesium.

[0021] Furthermore, the conductive agent is any one of acetylene black, graphite and carbon nanotubes, and the binder is any one of polyvinylidene fluoride PVDF, styrene butadiene rubber SBR and polytetrafluoroethylene PTFE.

[0022] Furthermore, the method of preparing the negative electrode active material in step 2 comprises the following steps:

[0023] Step 5: Converting expanded graphite into graphene using an improved Hummers method;

[0024] Step 6: Mix the graphene obtained in step 5 with a magnesium ion source and a polymer solid electrolyte to obtain a negative electrode material.

[0025] Furthermore, the mixing method in step one or step two is ultrasonic stirring.

[0026] Furthermore, in the ultrasonic stirring, the ultrasonic intensity is 70-100 Hz, the stirring speed is 5000-8000 r min-1, and the heating temperature is 75-85°C.

[0027] Compared with the prior art, the present invention provides a method for preparing a novel solid-state battery containing magnesium, which has the following beneficial effects:

[0028] The present invention not only prepares a new type of magnesium-containing solid-state battery, but also provides a new idea for the further application of new magnesium-containing graphene negative electrode materials in the field of solid-state batteries. In the preparation process, the traditional expanded graphite powder is first treated by the improved Hummers method to prepare low-cost, highly oxidized graphene; secondly, the magnesium source, graphene and polymer solid electrolyte are combined by ultrasonic stirring, which solves the problems of poor ionic conductivity of polymer solid electrolyte, easy aggregation of graphene and poor interface contact between magnesium-containing negative electrode active materials and solid electrolytes, and maintains the structural stability of graphene in the long cycle process, thereby effectively reducing the diffusion internal resistance of electrons and ions during the charge and discharge process, thereby achieving a substantial improvement in the rate performance and cycle life of solid-state batteries. In addition, the method provided by the present invention is simple in process, low in cost, safe and environmentally friendly, and the magnesium salt and polymer solid electrolyte have high dispersion on graphene, which is suitable for industrial development. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings of the embodiments will be briefly introduced below. It is obvious that the drawings in the following description only relate to some embodiments of the present disclosure, rather than limiting the present disclosure.

[0030] Figure 1 This is a SEM image of the negative electrode material in a new solid-state battery containing magnesium.

[0031] Figure 2 This is the SEM image of the comparative sample - graphene negative electrode material.

[0032] Figure 3 It is a comparison chart of the rate performance of the example sample and the comparative sample.

[0033] Figure 4 The figure shows the cycle performance comparison between the example sample and the comparative sample under 1C condition. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings of the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0035] Unless otherwise defined, the technical terms or scientific terms used in the present disclosure should be understood by people with ordinary skills in the field to which the present disclosure belongs. The words "first", "second" and similar words used in the present disclosure do not indicate any order, quantity or importance, but are only used to distinguish different components. The words "include" or "comprise" and similar words mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0036] Embodiment 1

[0037] A novel solid-state battery containing magnesium comprises a positive electrode, a solid electrolyte and a negative electrode. The positive electrode active material in the positive electrode comprises LiFePO4, and the negative electrode and the solid electrolyte are a composite of a negative electrode active material containing a magnesium ion source and a polymer solid electrolyte.

[0038] The magnesium ion source is a soluble magnesium salt, specifically any one of magnesium acetate, magnesium sulfate and magnesium nitrate.

[0039] The polymer solid electrolyte includes any one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG) and polydimethylsiloxane (PDMS).

[0040] The novel magnesium-containing solid-state battery is any one of a solid-state lithium-ion battery, a solid-state sodium-ion battery and a solid-state potassium-ion battery.

[0041] Preparation method of novel solid-state battery containing magnesium

[0042] Step 1: Mix LiFePO4, a conductive agent and a binder to obtain a positive electrode slurry, and apply the slurry on a positive electrode current collector, and obtain a positive electrode layer after drying and rolling.

[0043] The conductive agent is any one of acetylene black, graphite and carbon nanotubes.

[0044] The binder is any one of polyvinylidene fluoride PVDF, styrene butadiene rubber SBR and polytetrafluoroethylene PTFE.

[0045] Specifically:

[0046] A positive electrode slurry consisting of LiFePO4, acetylene black and PTFE in a mass ratio of 8:1:1 is coated on the surface of the aluminum foil, and the positive electrode layer is obtained by drying and rolling.

[0047] Step 2: Mix the negative electrode material, the conductive agent and the binder to obtain a negative electrode slurry, and apply the negative electrode slurry on the negative electrode current collector, and obtain a negative electrode layer after drying and rolling.

[0048] Wherein: the method for preparing the negative electrode active material comprises the following steps:

[0049] The expanded graphite is converted into graphene using the modified Hummers method;

[0050] The graphene obtained in step five is mixed with a magnesium ion source and a polymer solid electrolyte to obtain a negative electrode material.

[0051] Among them is

[0052] (I) Preparation of graphene: A small amount of expanded graphite powder was placed in a 500 mL beaker and placed in an ice water bath. Concentrated sulfuric acid (80-100 mL) and potassium permanganate (10-15 g) were added successively under stirring with a stirring paddle to obtain a dark green mixed solution. The mixed solution was then placed in a constant temperature water bath and stirred at 45°C for 1-3 h to obtain a brown mixed solution. 50 mL of distilled water was then added to the mixed solution and the temperature was adjusted to 95°C. After stirring for 15 min, 50 mL of distilled water and 2-4 mL of hydrogen peroxide (to remove residual MnO4) were added. - and MnO2), and stirred until the solution turned bright yellow; finally, the bright yellow mixed solution was washed with distilled water until neutral, centrifuged and dried to obtain graphene.

[0053] (II) Preparation of negative electrode precursor: a small amount of the graphene obtained above and 2% to 5% of the magnesium source are added to 50 mL of a deionized water solution, and the solution is placed in an ultrasonic cleaner (ultrasonic intensity is 70 to 100 Hz), and 4 to 6 mL of ethanol (dispersant) is added dropwise under the action of ultrasonic vibration until the mixture is uniformly mixed; then 2% of the polymer solid electrolyte is added to the solution under the action of a stirring paddle, and stirring is continued to obtain a composite mixed solution (stirring time is 6 to 8 hours, stirring speed is 5000 to 8000 r min -1 , the heating temperature is 75-85° C.); finally, the obtained composite mixed solution is placed in a vacuum drying oven at 110° C. and dried for 10-12 hours to obtain a negative electrode precursor.

[0054] (III) Negative electrode preparation: The negative electrode precursor obtained above was ground into fine powder using a mortar and placed in a tube furnace for heat treatment. The treatment conditions were: 1-3 °C min-1 in an inert gas atmosphere. -1 The heating rate is raised to 450°C and maintained for 4 to 6 hours. After cooling to room temperature, the samples are collected to obtain the final product, a magnesium-containing graphene-polymer solid electrolyte negative electrode material.

[0055] (IV) The preparation process of the negative electrode precursor of the comparative sample is the same as that of the example sample precursor, but no magnesium source is added and it is not mixed with the polymer solid electrolyte.

[0056] (V) 80% of the negative electrode material obtained above, 10% of acetylene black and 10% of PTFE were weighed and ground and mixed, and then a solvent NMP was added thereto to obtain a negative electrode slurry, which was coated on a copper foil, dried and rolled to obtain a negative electrode layer.

[0057] Step 3: Assemble the positive electrode layer, negative electrode layer and polymer solid electrolyte obtained in steps 1 and 2 into a new solid-state battery containing magnesium.

[0058] Specifically:

[0059] Solid-state battery preparation

[0060] The positive electrode sheet, solid electrolyte and negative electrode sheet obtained above were assembled into a solid-state battery (containing magnesium graphene-polymer solid electrolyte LiFePO4) and electrochemically tested using a blue-electric test system.

[0061] Example 2

[0062] The difference from Example 1 is that the amount of the polymer solid electrolyte added is changed so that the mass of the polymer solid electrolyte is 3% of the magnesium-containing graphene.

[0063] Example 3

[0064] The difference from Example 1 is that the amount of the polymer solid electrolyte added is changed so that the mass of the polymer solid electrolyte is 4% of the magnesium-containing graphene.

[0065] Example 4

[0066] The difference from Example 1 is that the amount of the polymer solid electrolyte added is changed so that the mass of the polymer solid electrolyte is 5% of the magnesium-containing graphene.

[0067] Scanning electron microscopy (SEM) tests were performed.

[0068] Figure 1 This is a SEM image of the magnesium-containing graphene-polymer solid electrolyte negative electrode material obtained in Example 1.

[0069] Figure 2 This is the SEM image of the conventional graphene negative electrode material obtained in Example 1.

[0070] It was observed that after the improved Hummers method and ultrasonic stirring treatment, it can be seen that the polymer solid electrolyte is evenly coated on the graphene surface, and the soluble magnesium salt is dispersed on the graphene surface in the form of tiny particles.

[0071] Conduct electrochemical performance tests.

[0072] Figure 3 It is the rate performance diagram of the example sample and the comparative sample.

[0073] It can be found that the rate performance of the example samples is greatly improved compared with the rate performance of the conventional comparison samples, especially under high rate conditions.

[0074] Figure 4 The figure shows the cycle performance comparison between the example sample and the comparative sample.

[0075] It can be found that under 1C conditions, the cycle performance of the example sample is better than that of the comparative sample. After 100 cycles, the capacity retention rate can reach 98%.

[0076] Table 1 shows the test results of the electrochemical properties of the novel magnesium-containing solid-state battery obtained in the examples.

[0077] Cycle performance Example 1 Example 2 Example 3 Example 4 <![CDATA[Initial cycle specific capacity at 0.5 °C (mAh g -1 )]]> 153.7 168.5 155.7 145.4 <![CDATA[Capacity after the 100th cycle at 0.5 °C (mAh g -1 )]]> 138.7 156.6 141.9 128.4 Capacity retention after 100 cycles 90.2% 92.9% 91.1% 88.3%

[0078] By observing Examples 1 to 4, it is found that changing the amount of polymer solid electrolyte added has a great influence on the performance of the solid-state battery, which is mainly manifested in: too low an amount of addition will make the SEI film of magnesium-containing graphene and the solid electrolyte thin and loose, significantly inhibiting the rapid transmission of ions during the charge and discharge process, thereby reducing the cycle performance of the solid-state battery; too high an amount of addition will expand the transmission path of ions between the magnesium-containing negative electrode material and the polymer solid electrolyte, increase the diffusion internal resistance of ions, and thus affect the cycle performance and rate performance of the solid-state battery. Preferably, the comprehensive performance of the solid-state battery is optimal when the addition amount is 3%.

[0079] In summary, the combination of magnesium source, graphene and polymer solid electrolyte by improved Hummers method and ultrasonic stirring not only alleviates the problems of poor ionic conductivity of polymer solid electrolyte, easy agglomeration of graphene and poor interface contact between negative electrode material and solid electrolyte, but also maintains the structural stability of graphene in the long cycle process, thereby significantly improving the transmission rate of electrons and ions during charging and discharging, thereby making the capacity of the solid-state battery reach 10Ah, and the capacity retention rate reaches 98% after 100 cycles.

[0080] There are a few points to note:

[0081] 1. In the drawings of the embodiments of the present disclosure, only the structures related to the embodiments of the present disclosure are involved, and other structures can refer to the general design.

[0082] 2. In the absence of conflict, the features of the same embodiment and different embodiments of the present disclosure may be combined with each other.

[0083] The above are only specific embodiments of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a novel magnesium-containing solid-state battery, characterized in that: The following steps are involved: Step 1), LiFePO4, a conductive agent and a binder are mixed to obtain a positive electrode slurry, which is then coated on a positive electrode current collector, and dried and rolled to obtain a positive electrode layer; Step 2), mixing the negative electrode active material, the conductive agent and the binder to obtain a negative electrode slurry, and coating the negative electrode slurry on the negative electrode current collector, drying and rolling to obtain a negative electrode layer; Step 3), assembling the positive electrode layer, negative electrode layer and polymer solid electrolyte obtained in step 1) and step 2) into a novel solid-state battery containing magnesium; weighing 80% of the obtained negative electrode material, 10% of acetylene black and 10% of PTFE, grinding and mixing, then adding solvent NMP thereto to obtain a negative electrode slurry, and coating it on a copper foil, drying and rolling to obtain a negative electrode layer; The conductive agent is any one of acetylene black, graphite and carbon nanotubes, and the binder is any one of polyvinylidene fluoride PVDF, styrene butadiene rubber SBR and polytetrafluoroethylene PTFE; The method of using the negative electrode active material in step 2) comprises the following steps: 2.1) The expanded graphite is converted into graphene by the improved Hummers method; Preparation of graphene: a small amount of expanded graphite powder is placed in a 500 mL beaker and placed in an ice water bath, and 80-100 mL of concentrated sulfuric acid and 10-15 g of potassium permanganate are added successively under the action of stirring with a stirring paddle to obtain a dark green mixed solution; the mixed solution is then placed in a constant temperature water bath and stirred at 45°C for 1-3 hours to obtain a brown mixed solution; 50 mL of distilled water is then added to the mixed solution and the temperature is adjusted to 95°C, and after stirring for 15 minutes, 50 mL of distilled water and 2-4 mL of hydrogen peroxide are added thereto, and stirred until the solution is bright yellow; finally, the bright yellow mixed solution is washed with distilled water until neutral, centrifuged and dried to obtain graphene; 2.2), the graphene obtained in step 2.1) is mixed with a magnesium ion source and a polymer solid electrolyte to obtain a negative electrode material; preparation of a negative electrode precursor: a small amount of the obtained graphene and 2% to 5% of the magnesium source are successively added to a 50 mL deionized water solution, and the solution is placed in an ultrasonic cleaner with an ultrasonic intensity of 70 to 100 Hz, and 4 to 6 mL of ethanol is added dropwise under the action of ultrasonic vibration until the mixture is uniformly mixed; then 2% of the polymer solid electrolyte is added to the solution under the action of stirring with a stirring paddle, and stirring is continued to obtain a composite mixed solution, the stirring time is 6 to 8 hours, the stirring speed is 5000 to 8000 r min -1 , and the heating temperature is 75 to 85°C; finally, the obtained composite mixed solution is placed in a vacuum drying oven and dried at 110°C for 10 to 12 hours to obtain a negative electrode precursor; Negative electrode preparation: The obtained negative electrode precursor was ground into fine powder using a mortar and placed in a tube furnace for heat treatment. The treatment conditions were: 1-3 °C min-1 in an inert gas atmosphere. -1 The heating rate is raised to 450°C and maintained for 4 to 6 hours; after cooling to room temperature, the mixture is collected to obtain the final product, namely, magnesium-containing graphene-polymer solid electrolyte negative electrode material; The mixing method in step 1) or step 2) is ultrasonic stirring; In the ultrasonic stirring, the ultrasonic intensity is 70-100 Hz, the stirring speed is 5000-8000 r min-1, and the heating temperature is 75-85°C.

2. The method for preparing a novel magnesium-containing solid-state battery according to claim 1, characterized in that: A novel solid-state battery containing magnesium prepared by the preparation method comprises a positive electrode, a solid electrolyte and a negative electrode, wherein the positive electrode active material in the positive electrode comprises LiFePO4, and the negative electrode and the solid electrolyte are a composite of a negative electrode active material containing a magnesium ion source and a polymer solid electrolyte; The magnesium ion source is a soluble magnesium salt, specifically any one of magnesium acetate, magnesium sulfate and magnesium nitrate; The precursor raw material of the negative electrode active material is expanded graphite; The polymer solid electrolyte includes any one of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylic acid, polyethylene glycol and polydimethylsiloxane; The novel magnesium-containing solid-state battery is any one of a solid-state lithium-ion battery, a solid-state sodium-ion battery and a solid-state potassium-ion battery.

Citation Information

Patent Citations

  • Preparation method of carbon-coated nitrogen-magnesium-doped porous silicon-based composite material and its application in lithium-ion batteries

    CN111082013B

  • Magnesium-doped vanadium pentoxide nanobelt positive electrode material, preparation method thereof and aqueous zinc ion battery

    CN111900398A

  • Preparation method of magnesium-doped cobalt liquid and nickel-cobalt-manganese ternary precursor

    CN113845157A

  • Manufacturing method of all solid state power lithium ion battery

    CN108232318A

  • Negative electrode for all-solid-state battery, manufacturing method thereof and all-solid-state battery

    CN114520337A